SYSTEM OF GUARANTEED RESOLUTION OF DYNAMIC CONFLICTS OF AIRCRAFTS IN REAL TIME - Pavlova, Svitlana; Volkov, Olexander (Proceedings of National Aviation University (archive), 2017)
Purpose: The present work is devoted to improving of flight safety in civil aviation by creating and implementing a new system of resolution of dynamic conflict of aircrafts. The developed system is aimed at ensuring a guaranteed level of safety when resolution of rarefied conflict situations of aircraft in real-time. Methods: The proposed system is based on a new method of conflict resolution of aircraft on the basis of the theory of invariance. Results: The development of the system of conflict resolution of aircraft in real time and the implementation of the respective algorithms such control will ensure effective prevention of dangerous approaches. Discussion: The system is implemented as single unified equipment using satellite and radar navigation systems that will ensure the positioning of aircraft in real time. Provided that the system should be installed on all aircraft and integrated on board to properly ensure its functionality and interact with navigation systems.